Fertility in Africa: Dynamics and Challenges of Development - Sene Abdourahmane Mbade (European Scientific Journal, ESJ, 2022)
This research is interested in the links between the fertility of women and the economic and social development of their country. It is part of an African context marked by weak indicators of economic and social development but with high indicators of demographic growth. Methodologically, quantitative data relating to demographic, economic, social and health variables are analyzed using a Principal Component Analysis, evolution curves, and projections to the year 2100. The results show that some African countries, despite their high fertility rates, benefit from social progress related to health and life expectancy even if their economy seems to be negatively affected especially by the high dependency indices of young people. Strong inequalities in fertility rates are also noted between different countries and different geographic regions, making the geography of the African population plural. The various demographic projections made show real opportunities for the continent's economic development in the future.